2018
DOI: 10.5888/pcd15.170320
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Health Professionals to Tweet About #HPVvaccine? Identifying Strategies for Effective Communication

Abstract: IntroductionWe conducted this study to quantify how health professionals use Twitter to communicate about the human papillomavirus (HPV) vaccine.MethodsWe collected 193,379 tweets from August 2014 through July 2015 that contained key words related to HPV vaccine. We classified all tweets on the basis of user, audience, sentiment, content, and vaccine characteristic to examine 3 groups of tweets: 1) those sent by health professionals, 2) those intended for parents, and 3) those sent by health professionals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 23 publications
1
45
1
1
Order By: Relevance
“…These results were quite contrary to past studies in which public discourse about the HPV vaccine were negative and controversial (Nan and Madden, 2012;Ruiz and Barnett, 2015). The change in discourse could be attributed to CDC efforts encouraging doctors to promote the HPV vaccine among teenagers (Jenco, 2019) and the active promotion of the HPV vaccine by health care professionals on social media (Massey et al, 2018).…”
Section: Discussioncontrasting
confidence: 66%
“…These results were quite contrary to past studies in which public discourse about the HPV vaccine were negative and controversial (Nan and Madden, 2012;Ruiz and Barnett, 2015). The change in discourse could be attributed to CDC efforts encouraging doctors to promote the HPV vaccine among teenagers (Jenco, 2019) and the active promotion of the HPV vaccine by health care professionals on social media (Massey et al, 2018).…”
Section: Discussioncontrasting
confidence: 66%
“…51 A study of 50 of the most recent Instagram posts available on September 7, September 21, and October 4 of 2018 that used the hashtag #HPV (for a total of 150 posts) found that 45% mentioned the HPV vaccine, and the majority of those posts were identified as being pro-vaccine (79.2%). 47 24 YouTube Vaccination and immunization All videos as of February 20, 2007 Ache (2008) 25 YouTube HPV vaccination All videos as of February 8, 2008 Briones (2012) 26 YouTube HPV vaccination All videos as of November 1, 2010 Basch (2017) 27 YouTube Anal cancer All videos with at least 1,000 views as of June 29, 2016 Basch (2016) 28 YouTube HPV Most viewed "consumer" and "professional" videos from 2007 and June 2014 Ekram (2018) 29 YouTube HPV vaccination Most viewed videos and top 100 comments from June 22, 2014 and December 19, 2014 Coloma (2015) 30 Facebook, Twitter, Google+ HPV and fertility All posts as of September 25, 2014 Suragh (2018) 31 Facebook Immunization adverse effects Top 20 posts from 2007 to 2016 about each topic: hysteria, fainting, and mystery illness after vaccination Hale (2014) 32 Facebook Health conditions All Facebook pages of 20 most searched for health conditions (HPV as #17) on Google as of July 24, 2012 Dunn (2015) 33 Twitter HPV vaccination All tweets from October 1, 2013 to April 1, 2014 Zhou (2015) 34 Twitter HPV vaccination All tweets from October 1, 2013 to March 31, 2014 Mahoney (2015) 35 Twitter HPV vaccination First 100 tweets that included news articles from April 1, 2011 to October 31, 2011 Bahk (2016) 36 Twitter Vaccination All tweets from August 2013 to July 2014 Massey (2016) 37 Twitter HPV vaccination All tweets from August 1, 2014 to July 31, 2015 Surian (2016) 38 Twitter HPV vaccination All tweets from October 1, 2013 to October 29, 2015 Du (2017) 39 Twitter HPV vaccination All tweets from November 2, 2015 to March 28, 2016 Dunn (2017) 40 Twitter HPV vaccination All tweets from October 1, 2013 to October 30, 2015 Keim-Malpass (2017) 41 Twitter HPV vaccination All tweet over two-week period in June 2015 Shapiro (2017) 42 Twitter HPV vaccination All tweets from Australia, Canada, and the UK from January 2014 to April 2016 Lama (2018) 43 Twitter HPV All tweets posted by users in the USA from November 11, 2014 to August 8, 2016 Massey (2018) 44 Twitter HPV vaccination All tweets from August 1, 2014 to July 31, 2015 Teoh (2018) 45 Twitter Cervical cancer Top tweets in January 2016 Keelan (2010...…”
Section: Content Valencementioning
confidence: 99%
“…29 The most common topics included in tweets about the HPV vaccine written by health professionals between August 2014 and July 2015 were about prevention and protection (35.5%, n = 302) with significantly less tweets about side effects (10.7%, n = 91) and risk or prevalence (10.3%, n = 88). 44 In an analysis of the top 35 videos about HPV from 2007 to June 2014 created by a nonprofit or health organization featuring one or more professionals with clinical credentials, the most common information included was HPV's association with cancer (97.1%), HPV screening (77.1%), how the virus is transmitted (65.7%), and prevention of HPV infection (60.0%). 28 Only 19 videos (54.3%) included any discussion of HPV vaccination, and five of these were discouraging against vaccination; nine were neutral.…”
Section: Negative Vs Positive Contentmentioning
confidence: 99%
See 2 more Smart Citations